Wood retention at inclined racks: Effects on flow and local bedload processes. Issue 9 (17th April 2020) - Schalko, Isabella
Abstract: Large wood (LW) transport can increase greatly during floods, leading to accumulations at river infrastructures. To mitigate the potential flood hazard, racks are a common method to retain LW upstream of endangered settlements or infrastructures. The majority of LW retention racks consist of vertical bars and, therefore, disrupt bedload transport. It can be hypothesized that inclined racks reduce backwater rise and local scour, as wood will block the upper part of the rack, thereby increasing the open flow cross‐section below the accumulation. Flume experiments were conducted under clear water conditions to analyse backwater rise and local scour as a function of (1) rack inclination, (2) hydraulic inflow condition, (3) uniform bed material, and (4) LW volume. In addition, the first experiments were performed under live bed scour conditions to study the effect of bedload transport on local scour and backwater rise. Based on the experiments, backwater rise and local scour decrease with decreasing rack angle to the horizontal. LW predominantly accumulated at the upper part of the rack, leading to an open flow cross‐section below the accumulation. The effect of rack angle was included in existing design equations for backwater rise and local scour depth. In addition, the first experiments with bedload transport resulted in smaller backwater rise and local scour depth. This study contributes to an enhanced process understanding of wood retention and bedload transport at rack structures and an improved design of LW retention racks. © 2020 John Wiley & Sons, Ltd. Abstract : Based on flume experiments under clear water and live bed conditions, backwater rise and local scour depth decrease with decreasing rack angle to the horizontal. Wood predominantly accumulated at the upper part of the rack, thereby maintaining a larger open flow cross‐section below the accumulation compared to vertical racks.